„Leporis vero si novellae…”, czyli o powiązaniu medycyny i sztuki kulinarnej w "De observatione ciborum" Antimusa - Rzeźnicka, Zofia (Vox Patrum, 2022)
The present study scrutinizes the initial part of the recipe considering culinary preparation of hare meat (reading: „Leporis vero si novellae…”), from a Byzantine medical treatise De observatione ciborum by Anthimus (5th/6th c. AD). The first part of the article proves that the work was written in accordance with the ancient materia medica. The author emphasises the specific character of the said work, as it discusses foodstuffs typical for non-Mediterranean peoples. Moreover, she highlights that since treatise was dedicated to Theuderic, the ruler of the Franks it contains mainly information on food served at the royal court. As an example showing Theuderic's high social status a recipe for hare meat is given. In the main part of the study the author analyses the initial passage of the said formula. On the basis of Anthimus' treatise as well as medical (works by Galen [2nd/3rd c. AD], Oribasius [4th c. AD], Aetius of Amida [6th c. AD]) and culinary (a poem by Archestratos of Gela [4th c. BC], De re coquinaria [4th c. AD]) sources she proposes a reconstruction of culinary technology which might have been recommended by Anthimus in preparing the examined dish. The comparative analysis of the above source material confirms Anthimus’ competences in the field of dietetics as well as a close connection between ancient/Byzantine medicine and culinary art. Furthermore, it proves that medical treatises are useful in the research on the history of everyday life.